Humoral Response to the Anopheles gambiae Salivary Protein gSG6: A Serological Indicator of Exposure to Afrotropical Malaria Vectors - Rizzo, Cinzia (Public Library of Science, 2011)
Salivary proteins injected by blood feeding arthropods into their hosts evoke a saliva-specific humoral response which can be useful to evaluate exposure to bites of disease vectors. However, saliva of hematophagous arthropods is a complex cocktail of bioactive factors and its use in immunoassays can be misleading because of potential cross-reactivity to other antigens. Toward the development of a serological marker of exposure to Afrotropical malaria vectors we expressed the Anopheles gambiae gSG6, a small anopheline-specific salivary protein, and we measured the anti-gSG6 IgG response in individuals from a malaria hyperendemic area of Burkina Faso, West Africa. The gSG6 protein was immunogenic and anti-gSG6 IgG levels and/or prevalence increased in exposed individuals during the malaria transmission/rainy season. Moreover, this response dropped during the intervening low transmission/dry season, suggesting it is sensitive enough to detect variation in vector density. Members of the Fulani ethnic group showed higher anti-gSG6 IgG response as compared to Mossi, a result consistent with the stronger immune reactivity reported in this group. Remarkably, anti-gSG6 IgG levels among responders were high in children and gradually declined with age. This unusual pattern, opposite to the one observed with Plasmodium antigens, is compatible with a progressive desensitization to mosquito saliva and may be linked to the continued exposure to bites of anopheline mosquitoes. Overall, the humoral anti-gSG6 IgG response appears a reliable serological indicator of exposure to bites of the main African malaria vectors (An. gambiae, Anopheles arabiensis and, possibly, Anopheles funestus) and it may be exploited for malaria epidemiological studies, development of risk maps and evaluation of anti-vector measures. In addition, the gSG6 protein may represent a powerful model system to get a deeper understanding of molecular and cellular mechanisms underlying the immune tolerance and progressive desensitization to insect salivary allergens.